Knowledge, prevalence and treatment practices of uterine prolapse among women of reproductive age in the Jhaukhel- Duwakot Health Demographic Surveillance Site, Bhaktapur, Nepal - Shrestha, Binjwala; Choulagai, Bishnu; Onta, Sharad; Shrestha, Khadga B; Petzold, Max; Krettek, A (Journal of Kathmandu Medical College, 2015)
Background: Uterine prolapse (UP) is a main contributor to reproductive health problems that infl uence women’s quality of life. In Nepal, the UP prevalence ranges from 7-27%. Women experience various diffi culties and symptoms due to UP, which are determined by the type as well as thestage of UP. Objectives: This study aimed to explore the knowledge, prevalence and treatment practices of uterine prolapse among women of reproductive age in the peri-urban Jhaukhel-Duwakot Health Demographic Surveillance Site (JD-HDSS) in the Bhaktapur district of Nepal. Methods: This cross-sectional study collected data in two stages. A structured survey of 3,124 households in JD-HDSS, incorporating 60% of all women of reproductive age, assessed knowledge of uterine prolapse and identifi ed self-reported disease prevalence (symptomatic). Next, we organised a fi ve day clinical screening camp at JD-HDSS to identify the prevalence of uterine prolapse in attendees.The household survey was conducted on September-December 2012 and the UP screening camp on May-June 2013. Descriptive statistics was used to analyse the proportion of comprehensive knowledge regarding UP and the prevalence of UP. Results: Ninety-three percent of womenin JD-HDSS had heard of uterine prolapse and 55% of those had comprehensive knowledge. Self-reported (symptomatic) prevalence was 2.11% (8.5% including women who had undergone hysterectomy for uterine prolapse). Among these, 52.6% had received no treatment. The most common reported treatments of uterine prolapse included surgery (53.2%), exercise and medicine (35.5%) and pessary (11.3%). Among women attending the outreach camp (N=303), UP prevalence was 15.18%. Conclusion: Knowledge of uterine prolapse among women in JD-HDSS is almost double that reported in a national survey. Similarly, the prevalence of self-reported uterine prolapse in JD-HDSS is almost three fold less than the national prevalence. Knowledge,early healthcare practices and availability of surgical care for uterine prolapse might have contributed to these fi ndings. Journal of Kathmandu Medical College Vol. 3, No. 4, Issue 10, Oct.-Dec., 2014 Page: 136-143